ICR: information, cluster and route agent based method for efficient routing in VANET - Gokula Krishnan, V; N. Sankar Ram, Dr (International Journal of Engineering and Technology, 2018)
Vehicular Ad-Hoc Network (VANET) is a variety of mobile ad-hoc networks (MANET) that differs from the fact that VANETS communicates between vehicle-to-vehicle and vehicle-to-roadside communication network. VANETs have the possibility to integrate with WiFi, Bluetooth and other connectivity protocols which makes it a new standard. The desired outcome expected from VANET is to communicate between nodes in any environment irrespective of traffic density and vehicle locations. Since vehicular communication is a part of constantly changing environment and it must also operatein urban and rural areas. Taking in mind the large number of nodes that are actually participating in these networks and also the property of high mobility between them, it has resulted in many debates about a feasible routing protocol. This paper introduces a multi-agent system approach to solve the problems faced by vehicular communications since it comprises of more than one agent solve the problem of routing, the resulting protocol gives higher efficiency and better performance on packet delivery and end-to-end packet delay.